A Socio-Health Reading of Health Education as a Preventive Mechanism in Society - Aida, Meguellati (Journal of Ecohumanism, 2026)
Health education forms an entire operation that aims to improve consciousness and health knowledge. It reinforces positive behaviour on individual and society level, and it covers various fields of nutrition and physical activity to mental and sexual health. It includes positive changes in awareness and behaviour. Health educational efforts contributes in reducing the spread of diseases and improving the quality of life. The outcomes are reflected in the enhancement of individual and collective well-being, and in the formation of healthy and sustainable communities.